(untitled) (American Journal of Islam and Society, 1994)
This book features a selection of articles dealing with interest (riba) and other related issues and is mainly an appraisal of the interest-free system as an alternative to the western fixed-rate system. Seven essays deal with the experience of Islamic banking in Pakistan. Ziauddin Ahmed and Nawazish A. Zaidi highlight some of the concerns associated with implementing Islamic banking practices. Although these cancems ate quite real, the appmh is more anecQtal than empirical. nK essays of Ghulam Khan, D. M. Qureshi, and Tariq Hassan, as well as the State Bank of Pakistan’s article on Islamic modes of financing, provide prudent descriptions of how Islamic financial instnunen ts have been implemented in Pakistan. They also discuss various problems, a common one being that most (if not all) Islamic countries ate developing countries and, therefore, the transition to Islamic banking is inseparable from the mdimentary nature of their present banking systems. Jalees A. Faruqui’s article analyzes some of the ideological diffemces between the Islamic, capitalist, and socialist ecoflofILic systems. The capitalist system is Qminated by individualism and selfintetest, whems a staple element of the socialist system is the concept of class warfare. The Islamic system differs from the other two in one important way: it gives people individual rights, but in the context of caring for others. ’This characteristic means that an equitable distribution of h m e is an inherent, rather than an institutionalized, part of the system The final article in this section, by Haqqani, makes the point that a mudarbah certificak is nothing but a share certificate ...